CRITICAL INCIDENTS IN TEACHER EDUCATION - Łukasik, Joanna Małgorzata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This paper focuses on teacher as the person responsible for preparing pupils to a life in the world of changes. To enable this process, teachers themselves must possess the ability to adapt to changing circumstances. Biographical research (using diaries) conducted in the school year 2014/2015 in a group of teachers reveals that they do not cope well with disciplinary challenges in the class. Such an ability may be acquired not only by extending their knowledge, but also through referring to the knowledge already possessed, reflection-on-action and reflection-in-action. Acquisition of this ability is possible because of the analysis of critical incidents.